2020
DOI: 10.3390/en13040952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Evaporation and Condensation Heat Transfer Coefficients on the External Surface of Tubes in the Annulus of a Tube-in-Tube Heat Exchanger

Abstract: An experimental study was carried out to explore the heat transfer characteristics on the outside of smooth and enhanced tubes, during evaporation and condensation of R134A in the annulus of a tube-in-tube heat exchanger. The three-dimensional enhanced surface tube consisted of primary enhancement patterns and secondary patterns; results were compared to the performance of an equivalent smooth tube. The equivalent external diameter of the inside horizontal copper tubes used in this study was 19.05 mm, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the next paper, "Comparison of the Evaporation and Condensation Heat Transfer Coefficients on the External Surface of Tubes in the Annulus of a Tube-in-Tube Heat Exchanger", the authors, Tang et al [101], investigated the influence of the tube surface in a heat exchanger on the efficiency of heat transfer. They compared a tube with a smooth surface and a tube in which the dimples were arranged along the surface in a certain pattern.…”
Section: Heat Integration and Heat Transfermentioning
confidence: 99%
“…In the next paper, "Comparison of the Evaporation and Condensation Heat Transfer Coefficients on the External Surface of Tubes in the Annulus of a Tube-in-Tube Heat Exchanger", the authors, Tang et al [101], investigated the influence of the tube surface in a heat exchanger on the efficiency of heat transfer. They compared a tube with a smooth surface and a tube in which the dimples were arranged along the surface in a certain pattern.…”
Section: Heat Integration and Heat Transfermentioning
confidence: 99%
“…The main observations were that, with respect to smooth tubes, dimpling of the horizontal tube could increase the HTC rate by up to 70% while dimpling of the helical tube increased the HTC by as much as 88%. Tang et al [19] experimentally studied the effect on the condensation process of dimpling the outer surface of the inner tube of a co-axial tube-within-a-tube heat exchanger. They demonstrated that condensation was enhanced by approximately 178% for a dimpled inner tube compared to a smooth tube.…”
Section: Introductionmentioning
confidence: 99%